KUALITAS PELAYANAN RSUD PESAWARAN (STUDI PADA INSTALASI GAWAT DARURAT) (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2018)
The implementation of quality health services is one of the matters submitted to the regional government. This study aims to describe the quality of care for Emergency Room Installation (IGD) of the Regional Public Hospital of Pesawaran District with a focus on the variables of satisfaction, responsiveness, responsibility, transparency, accountability, and fairness. Through a descriptive qualitative approach the results of the study show that the quality of service in the IGD of RSUD Pesawaran District is quite good. It is necessary to procure a suggestion box for the absorption of aspirations from the people placed in a place that is easily seen as a form of input from the community in an effort to improve services. Pesawaran District Hospital also needs to improve the completeness and availability of medical devices, the feasibility of the room, the cleanliness of the action room and the patient's bathroom, and to improve the safety and comfort of the environment of the emergency room.